Ossification of Metacarpal in Prenatal Goat (Capra hircus) - Chaudhary, Avnish (Indian Journal of Veterinary Anatomy, 2019)
Present study was conducted on the metacarpals of goat, irrespective of sex and breed from 35-148 days of gestation. At 51 days of gestation, the cartilaginous miniatures of two metacarpals (III and IV) were present. At 55 days of estation, the centres of ossification for the diaphysis of both the metacarpals were exhibited. The center of ossification for the fifth metacarpal was exhibited at the lateral surface of fourth metacarpal bone at 62 days of gestation. At 82 days of gestation, the shaft of two metacarpals appeared to be fused together, which were completely fused on 101 days of gestation. The centre of ossification for distal extremity was exhibited at 135 days of gestation. At 148 days, the metacarpal was ossified completely and the vascular groove was more prominent in the distal 2/3 part.